IDENTIFICATION OF INITIAL COVID-19 IMPORT AND DISSEMINATION ROUTES IN BRAZIL - Pereira, Vítor Hugo Campelo; Diniz, Marco Túlio Mendonça; Rocha, Glairton Cardoso; Oliveira Júnior, Marcos Antonio Cavalcante de (Geosaberes; Vol 11 (2020): Vol 11 (2020)DO - 10.26895/geosaberes.v11i0.1043, 2020)
This article aimed to identify, in the context of the aviation structure, the initial routes of entry of COVID-19 into Brazil in each Brazilian state. From the survey of epidemiological data about the first cases of COVID-19 recorded in each Brazilian state, airport and air transport information, the initial routes for insertion and dissemination of COVID-19 were identified and spatialized. The results showed that the main initial routes of transmission and dissemination of this disease in Brazil are of international origin, mainly from the European continent and national origin, especially from the states of São Paulo and Rio de Janeiro. The way in which COVID-19 was introduced in Brazil and its initial dissemination was directly related to the direction of the flows of convergent people and goods to the main management centers in the country, mainly through air transport.